METHOD OF PROJECTS IN EXTRACURRICULAR VOCAL AND CHORAL ACTIVITIES OF ADOLESCENTS - Мартьянова, Г. М. (Pedagogy of Higher and Secondary Education, 2011)
Considering pedagogical and creative conditions of the organization of out-class and out-school activity of teenagers, in article we research a problem formation of art-creative requirements and orientations of lyceum students, applying a method projects by the exam of creative collectives - choir of Dolgincevsky humanities-technical liceum of Krivoi Rog and choir of Novoivanivjska school.